Responsiveness to exogenous gonadotrophin on post-partum fertility during breeding and non-breeding seasons in buffaloes - Kumar, Rajesh; Phogat, J. B.; Sharma, Rakesh Kumar; Phulia, S. K.; Bangar, Yogesh; Andonissamy, Jerome (Frontiers in Animal Science, 2025)
The present study was designed to investigate the responsiveness to exogenous gonadotrophin on post-partum fertility during breeding and non-breeding seasons in buffaloes. During the breeding season, twenty-two post-partum buffaloes that calved between September and February were included and further divided into two groups: treatment (n = 12) and control (n = 10). Buffaloes in the treatment group received an exogenous GnRH analogue (Receptal; 10 µg buserelin acetate, i.v.) on day 21 post-partum, whereas the control group received no treatment. During the non-breeding season, post-partum buffaloes (n = 20) that calved between April and August were divided into two groups, treatment (n = 10) and control (n = 10), and the treatment group received exogenous GnRH analogue (Receptal; 10 µg buserelin acetate, i.v.) on day 21 post-partum. During breeding season, average pre-treatment LH concentration was similar in both treatment (1.7 ± 0.3 ng/ml, n=8) and control (1.2 ± 0.2 ng/ml, n=8) groups. During non-breeding season, pre-treatment LH concentration was comparable in both treatment (0.8 ± 0.1 ng/ml, n=8) and control (0.9 ± 0.2 ng/ml, n=8) groups. The basal LH level was lower (P < 0.05) during the non-breeding season compared with that during the breeding season (0.88 ± 0.1 ng/ml, n=16 vs 1.44 ± 0.2 ng/ml, n=16). GnRH administration on day 21 post-calving has been found to improve the early resumption of cyclicity during breeding calved (83.3%) and non-breeding calved buffaloes (80%) by day 28 post-partum. Administration of GnRH helped resume early cyclicity in all animals during both seasons. Following GnRH administration, cyclicity resumed in 82% of the treatment group and 45% of the control group on day 28 post-calving. By day 60 post-partum, 95.5% and 75% of buffaloes in the treatment and control groups, respectively, had resumed cyclicity. GnRH administration on day 21 post-calving did not influence conception rate, as overall conception rates within three inseminations were similar in the treatment and control groups during the breeding season (75% vs. 70%). In conclusion, administration of GnRH post-partum aids early resumption of ovarian cyclicity and reduces days open in buffaloes, irrespective of season.